Odysseus inside the Cyclop’s cave: Turnaround strategy and leadership insights from the struggle against Polyphemu - Α. Kakaletris, Panagiotis; Kopsidas, Odysseas (Edelweiss Applied Science and Technology, 2024)
The present study aspires to perform a thorough examination of the notion of turnaround strategy process within the context of Homer’s Odyssey. More specifically, focusing on Odysseus’ struggle against the one-eyed Cyclop, Polyphemus, we seek to draw some interesting insights into the way a turnaround process unfolds, as well as its key attributes and components. Although the topic of turnaround strategy has attracted significant research attention over the last 50 years, the vast majority of extant studies has focused on the practices of formerly declining companies which mainly originate from developed countries. Furthermore, most of the existing studies are based on quantitative research methodologies, such as large sample surveys. The novelty of the present study is associated with the adoption of a multidisciplinary perspective, whereby modern strategic management and leadership theories are applied in order to analyze and interpret one of the greatest masterpieces of global literature, Homer’ Odyssey. This objective is attained through the employment of a qualitative, case study research methodology. More specifically, the symbolic analysis of Odyssey’s Book 9, indeed yielded some very interesting insights regarding the way a representative turnaround process unfolds, as well as the importance of effective leadership as part of such processes. Based on Odysseus’ actions and behaviors toward his companions during this crisis situation, we conclude that transformational leadership may be the most appropriate leadership style under extraordinary and emergency circumstances.